Learning and training while serving time - Perla Arianna Allegri (Oñati Socio-Legal Series, 2025)
The article presents the results of empirical research on vocational training activities within the Italian prison context. The research constitutes an attempt to bring rehabilitation rhetoric into dialogue with the practices that emerged from the interviews conducted with inmates, educators and vocational trainers, through the lens of prison sociology. In particular, the paper delves into the dynamics of professional cultures within the Italian prison system, exploring how norms inherent to the teaching professions intersect with the institutional environment and actors. The aim of this paper is to reconstruct the fragmentary nature of penal control exercised in the prison environment through the recomposition of the framework of interactions occurring among different professional and legal cultures of educators, prison officers and vocational experts.